Comportamento do consumidor na rede: o caso AREZZO no Facebook - Lacerda, Alana Bauer (Universidade do Vale do Rio dos Sinos, 2011)
This study aims to understand the consumer power in the social webs, especially Facebook. On the current context, in which consumer knows his individuality and aspires to defend his interests, internet has come as an able vehicle to empower his communication with a brand or a company. Buzz marketing is characterized as a consequence of this new context: interesting messages for people are spread on the web like a virus and, in some days, become known to thousands of people. This is what happened to the company of women shoes that was the study object of this thesis: Arezzo, in April 2011, launched the collection named Pelemania, which had parts made of animal skin. Due to the consumer protests on the internet, in some days the company decided to remove the collection from stores. The tools used to this study were documentary analysis on journalistic material about the case, content analysis on Facebook fan pages “Arezzo” and “Boicote Arezzo” and interviews. The conclusions lead to the fact that consumers have a elevated power of talking and influence with brands. However, even when disseminating negative messages, it may cause an increase in brand remembrance and a consequent increase in sales, as it occurred with Arezzo.
Keywords: Poder do consumidor; Facebook; Marketing viral; Consumer power; Facebook; Buzz marketing